Knowledge translation in healthcare - Kitson, Alison L; Wiechula, Rick; Salmond, Susan Warner; Jordan, Zoe (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
The publication focuses on translating evidence into action in medical policy and practice. Written as a guide for professionals.
Synthesis science in healthcare series ; Book 12
Keywords: směrnice pro lékařskou praxi jako téma; management, organizace a řízení zdravotnictví; Evidence-Based Medicine; Health Policy; Practice Guidelines as Topic; translační biomedicínský výzkum; zdravotní politika; Translational Research, Biomedical; medicína založená na důkazech